A Review of Environmental, Social and Governance (ESG) Regulatory Frameworks: Their Implications on Malaysia - Tang, Kuok Ho Daniel (Tecno Scientifica Publishing, 2023)
The increasing emphasis on sustainability has led many nations to introduce ESG-related regulatory frameworks. These frameworks aim to regulate and guide financial investments based on the ESG performance of companies while ensuring transparency to prevent the manipulation of sustainability-related information concerning investment products. This article reviews the regulatory and disclosure frameworks implemented in different nations and regions to identify their key components. The review reveals that these regulatory frameworks capture the environmental aspects encompassing climate change adaptation and mitigation, identification, evaluation and management of climate risks, circular economy practices, and pollution prevention. They also cover the social aspects, which include community development, employee welfare, and human rights. Additionally, governance aspects comprising anti-corruption measures, diversity within company boards and management, and the implementation of due diligence were included. The increased emphasis on transparency underscores the importance of disclosure. In this regard, the disclosure frameworks largely align with the recommendations of the Task Force on Climate-related Financial Disclosures, which cover governance, strategies for identifying and assessing risks and opportunities, their impacts on a company's finances and operations, resilience-building through scenario analyses, risk management integration with the overall organizational risk management, and the use of metrics and targets to measure performance. Malaysia could benefit from adopting comprehensive regulatory and disclosure frameworks that address ESG holistically, with elements related to the circular economy and dual materiality included in the frameworks. Future studies could focus on standardizing the development of metrics and targets to facilitate performance comparisons.